THE VERBAL CULTURE OF AN ENGLISH TEACHER - Tursunoy, A.U. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
This article examines the features of the teacher's speech behavior in an English. This article discusses that verbal culture and the ability to communicate, interact. The verbal culture plays a huge role in creating a positive atmosphere, communication between communicators and as well as in the socialization of students. Also the article The article also states that verbal culture is a skill that a teacher must acquire and a very important key component. There is no doubt that a teacher who has mastered the culture of speech is definitely a successful teacher.
Keywords: verbal culture; teacher's image; speech means; communication; culture of speech; culture; education; language